The Role of Somatostatin Treatment in the Management of Chylous Fistula after Neck Dissection - Nilda Süslü; Bülent Sözeri; Ali Şefik Hoşal; Metin Demircin (Turkish Archives of Otorhinolaryngology, 2014)

(untitled)
Chylous fistula is a serious complication of neck dissection. The use of somatostatin after neck surgery, has been described in literature. Because of the absence of definitive guidelines, reporting of our experience in three cases may guide the surgeons to overcome this life threatening complication. We descibe three cases who underwent neck dissection. While two of them had high output (>1000 mL/day), one had a low output (250 mL/ day) chyle leakage, after neck dissection. After it was noticed in earlier days, conservative management was started immediately. While Somatostatin was started after the re-exploration in two, it was started due to the failure of conservative treatment for low output leakage in one. All of the chyleous fistulas were healed within less than two weeks. We think that somatostatin may be considered as an effective treatment in low output chyle fistulas which the leakage continues after conservative treatment; however in high output chyle fistulas, somatostatin should be used in patients due to lack of control of leakage after ligation of thoracic ductus in revision Somatostatin treatment was discussed in the light of the current literature.